Hubungan Tingkat Pengetahuan Pasien Tentang Tindakan Operasi dengan Tingkat Kecemasan Pasien Preoperasi Tindakan Orif di Instalasi Bedah Sentral Rumah Sakit Urip Sumoharjo Bandar Lampung - Muhammad Wiwit; Hardono Hardono; Eko Wardoyo (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Surgery is an invasive medical procedure that often causes anxiety in patients, especially in the preoperative phase. One of the factors that affect the level of anxiety is the patient's knowledge of the surgery to be undergone. This study aims to determine the relationship between the level of patient knowledge about the surgical procedure and the level of preoperative anxiety of the Open Reduction Internal Fixation (ORIF) action at the Central Surgical Installation of Urip Sumoharjo Hospital, Bandar Lampung. The study used an analytical quantitative design with a cross sectional approach. The sample amounted to 37 respondents who were selected through purposive sampling technique. The research instruments were in the form of a knowledge level questionnaire and the Hamilton Rating Scale for Anxiety (HRS-A). Data analysis was carried out univariate and bivariate with Gamma test. The results showed that the majority of respondents had a low level of knowledge (73.0%) and experienced severe anxiety (56.8%). The Gamma test yielded a p-value = 0.003 (< 0.05) with a Gamma coefficient of -0.880, indicating a significant, strong, and negative relationship between the level of knowledge and anxiety. The higher the patient's knowledge, the lower the level of anxiety experienced. These findings confirm the importance of preoperative education for patients to lower anxiety and improve readiness for surgical procedures.